5-ketoreductase from Streptomyces bingchengensis: overexpression and preliminary characterization - Wang, Xiang-Jing; Wang, Cheng-Qin; Sun, Xiao-Lin; Xiang, Wen-Sheng (Biotechnology letters, 2010)
To elucidate the biotransformation from 5-oxomilbemycins A₃ and A₄ to milbemycins A₃ and A₄ in Streptomyces bingchengensis, the C5-ketoreductase gene (milF) was cloned using PCR with the specific primer designed from homologous nucleotide sequences. The C5-ketoreductase (MilF) was heterologously expressed in E. coli BL21 (DE3) as a His-tagged fusion protein. The characterization and biotransformation function of purified MilF was verified by in vitro enzyme assay. MilF is an NADPH-dependent reductase. The biotransformation products, analyzed by LC-APCI/MS, were identified as milbemycin A₃ and milbemycin A₄. MilF is thus present in Streptomyces bingchengensis and can transform 5-oxomilbemycins A₃ and A₄ to milbemycins A₃ and A₄. These findings are significant for understanding the biosynthetic pathway of milbemycins in Streptomyces bingchengensis and pave the way to obtain a producer strain of 5-oxomilbemycins directly by targeted milF disruption.